Meckel’s Diverticulitis: A Rare Cause of Peritonitis in Children - Kalli, Moussa; Bembo, Lamega; Ngaringuem, Olivier; Abakar, Mahamat Nour; Younous, Seid; Abdelkerim, Nedjim; Ouchemi, Choua (European Scientific Journal, ESJ, 2025)
Peritonitis is a rare complication of Meckel’s diverticulum. It is difficult to diagnose in a resource-limited setting. We report the case of a 9-year-old patient treated in the paediatric surgery department of the Centre Hospitalier Universitaire de la Mère et de l’Enfant in N’Djamena for acute peritonitis, with intraoperative findings of Meckel’s diverticulitis with suspicious peritoneal effusion. Segmental resection of the small intestine was performed, removing the diverticulum, followed by immediate anastomosis. The patient was discharged on the eighth postoperative day with no complications. Conclusion: Meckel’s diverticulitis is rare and difficult to diagnose in a resource-limited setting. Its treatment is essentially surgical.